Preconception laparoscopic transabdominal cervicoisthmic cerclage (TAC) placed in older women - Pawłowicz, Paweł; Uchman-Musielak, Małgorzata; Hincz, Piotr; Jakiel, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2012)
We report a case of a 38-year-old patient with a history of recurrent miscarriages, with the diagnosis of cervical incompetence, in whom transvaginal cerclage was not technically possible and preconception laparoscopic transcervical abdominal cerclage was performed. The operation lasted for 30 minutes and was completed successfully. The patient was discharged the next day. The patient became pregnant two months later, the course of pregnancy was physiological and she gave birth at term by a cesarean section to a female newborn with a weight of 3450g and 10 points in Apgar score.